Irreversible Electroporation Plus Anti-PD-1 Antibody versus Irreversible Electroporation Alone for Patients with Locally Advanced Pancreatic Cancer - He C; Sun S; Zhang Y; Li S (Dove Medical Press, 2021)
Chaobin He,1,* Shuxin Sun,2,* Yu Zhang,3,* Shengping Li1 1Department of Pancreatobiliary Surgery, State Key Laboratory of Oncology in South China, Collaborative Innovation Center for Cancer Medicine, Sun Yat-sen University Cancer Center, Guangzhou, 510060, People's Republic of China; 2Department of General Surgery, Guangdong Provincial People's Hospital, Guangdong Academy of Medical Sciences, Guangzhou, Guangdong Province, People's Republic of China; 3State Key Laboratory of Ophthalmology, Zhongshan Ophthalmic Center, Sun Yat-sen University, Guangzhou, Guangdong, 510060, People's Republic of China*These authors contributed equally to this workCorrespondence: Shengping Li Email lishengp@mail.sysu.edu.cnBackground: Irreversible electroporation (IRE) is shown to not only improve the prognosis of patients with locally advanced pancreatic cancer (LAPC) but also activate the immune system. Considering the immune-activating function of IRE, IRE may enhance the effect of immune checkpoint inhibitors in the treatment of LAPC. We aimed to compare the effect and safety of IRE combined with toripalimab versus IRE alone for LAPC.Methods: We retrospectively collected data from LAPC patients treated with IRE plus toripalimab (240mg, 7 days after IRE) or IRE alone at Sun Yat‑sen University Cancer Center. Overall and progression-free survival and treatment-related adverse events were evaluated and compared.Results: From August 2015 to June 2020, a total of 85 patients were collected and analyzed in this study: 70 in the IRE group and 15 in the IRE plus toripalimab group. The IRE plus toripalimab group showed longer OS [44.33 months (95% CI 17.39- 71.27) versus 23.37 months (95% CI 21.20- 25.54), P=0.010] and PFS [27.5 months (95% CI not reached) versus 10.6 months (95% CI 7.79- 13.42), P=0.036], compared with IRE group. There were no treatment-related deaths in all patients of this study. Although pancreatic fistula, biliary fistula, abscess, vomiting and gastroparesis were a little more common in IRE plus toripalimab group, no significant differences in the rates of all adverse events between these two groups were observed.Conclusion: IRE plus toripalimab had acceptable toxic effects and might improve survival in LAPC compared with IRE alone.Keywords: locally advanced pancreatic cancer, irreversible electroporation, toripalimab, efficacy, prognosis